A review: calcium carbonate (CaCO3) extract from natural ceramics for thin film application - Zulkefli, Nursyazwani; M. Yusup, Eliza; Othman, Mohd Hilmi (2021)
CaCO3 are widely used as one of the main materials in bone tissue engineering. The biodegradable material used is thin films and has been widely recognized as a prospective approach to altering a biomaterial's surface properties. Ideal thin films must be able to imitate mechanical and biological properties besides being able to support the growth of large tissue constructions. Different uses of procedures, tools and processing requirements have led to the development of several layer-by-layer assembly techniques that widely used in porous membranes, particles and biological matters. Employing new ways of nature-based materials such as mineral products extracted from CaCO3 has caused the increasing demands of natural materials that can be easily fulfil by using cockle shells, eggshells, or fish scales as main sources as well as due to their availability and low cost. The thin film in this research is expected to get incorporated at bone surfaces to control tissue-biomaterial interaction and have mechanical properties that are similar to the soft biological tissues. This paper review has 5 related sub-topics; 1. Introduction, 2. Biomaterial in Tissue Application, 3. Usage of Natural Ceramics in Bone Tissue Application, 4. Polymer in Biomedical Application and 5. Summary